Modified Carbon Nanofibers CNFs from Electrospun Polyacrylonitrile and Carbon Nanotubes PAN/CNTs - Yahya, Fatima M.; Najim, Manar A.; Hamza, Mohammed S. (Iraqi Journal of Science, 2026)
This study introduces a method to enhance the graphitization of carbon nanofiber (CNFs) by incorporating multi walled carbon nanotubes (MWCNTs) to polyacrylonitrile (PAN) as precursors to improve graphitization compared to CNFs produced from pure PAN precursors. Both traditional CNFs and modified CNFs/CNTs were synthesized via electrospinning followed by thermal treatment (stabilization at 275°C and carbonization at 1000°C in N2 gas atmosphere). FE-SEM analysis showed a reduction in average fiber diameter after the addition of MWCNTs. Post-carbonization, the composite CNFs/CNTs exhibited a smaller diameter reduction (−13.54%) compared to pure CNFs (−25.05%), indicating enhanced structural stability. FTIR spectroscopy confirmed the effectiveness of adding MWCNTs to the graphitization process. XRD analysis revealed the successful carbonization of both CNFs and CNFs/CNTs specimens at 1000°C while Raman spectroscopy showed a slight decrease in ID/IG intensity ratio from 1.22 for CNFs to 1.15 for CNFs/CNTs. Both the electrical conductivity and water contact angle were enhanced in the modified CNFs/CNTs compared with the traditional CNFs.